Synthesis of esters of diaminotruxillic bis-amino acids by Pd-mediated photocycloaddition of analogs of the Kaede protein chromophore - Urriolabeitia, Esteban P.; Sánchez, Pablo; Pop, Alexandra; Silvestru, Cristian; Laga, Eduardo; Jiménez, Ana I.; Cativiela, Carlos (Beilstein Journal of Organic Chemistry, 2020)
The stereoselective synthesis of truxillic bis-amino esters from polyfunctional oxazolones is reported. The reaction of 4-((Z)-arylidene)-2-(E)-styryl-5(4H)-oxazolones 2 with Pd(OAc)2 resulted in ortho-palladation and the formation of a dinuclear open-book complexes 3 with carboxylate bridges, where the Pd atom is C^N bonded to the oxazolone. In 3 the two exocyclic C=C bonds of the oxazolone are in a face-to-face arrangement, which is optimal for their [2 + 2] photocycloaddition. Irradiation of dimers 3 in CH2Cl2 solution with blue light (465 nm) promoted the chemo- and stereoselective [2 + 2] photocycloaddition of the exocyclic C=C bonds and the formation of cyclobutane-containing ortho-palladated complexes 4. Treatment of 4 with CO in a MeOH/NCMe mixture promoted the methoxycarbonylation of the palladated carbon and the release of the corresponding ortho-functionalized 1,3-diaminotruxillic bis-amino esters 5 as single isomers.
Keywords: amino acids; C–H activation; Kaede protein; oxazolones; photocycloaddition

(untitled) - Liebermann, C.; Giesel, F. (Ber. Dtsch. Chem. Ges., 1888)

(untitled) - Nakamura, M.; Chi, Y.-M.; Yan, W.-M.; Yonezawa, A.; Nakasugi, Y.; Yoshizawa, T.; Hashimoto, F.; Kinjo, J.; Nohara, T.; Sakurada, S. (Planta Med., 2001)

(untitled) - Chi, Y.-M.; Nakamura, M.; Yoshizawa, T.; Zhao, X.-Y.; Yan, W.-M.; Hashimoto, F.; Kinjo, J.; Nohara, T.; Sakurada, S. (Biol. Pharm. Bull., 2005)

(untitled) - Chi, Y.-M.; Nakamura, M.; Zhao, X.-Y.; Yoshizawa, T.; Yan, W.-M.; Hashimoto, F.; Kinjo, J.; Nohara, T.; Sakurada, S. (Biol. Pharm. Bull., 2006)

(untitled) - Chi, Y.-M.; Nakamura, M.; Zhao, X.-Y.; Yoshizawa, T.; Yan, W.-M.; Hashimoto, F.; Kinjo, J.; Nohara, T.; Sakurada, S. (Biol. Pharm. Bull., 2006)

(untitled) - Rupp, M.; Schroeter, T.; Steri, R.; Zettl, H.; Proschak, E.; Hansen, K.; Rau, O.; Schwarz, O.; Müller-Kuhrt, L.; Schubert-Zsilavecz, M.; Müller, K.-R.; Schneider, G. (ChemMedChem, 2010)

(untitled) - Berger, W. T.; Ralph, B. P.; Kaczocha, M.; Sun, J.; Balius, T. E.; Rizzo, R. C.; Haj-Dahmane, S.; Ojima, I.; Deutsch, D. G. (PLoS One, 2012)

(untitled) - Yan, S.; Elmes, M. W.; Tong, S.; Hu, K.; Awwa, M.; Teng, G. Y. H.; Jing, Y.; Freitag, M.; Gan, Q.; Clement, T.; Wei, L.; Sweeney, J. M.; et al. (Eur. J. Med. Chem., 2018)

(untitled) - Kaczocha, M.; Rebecchi, M. J.; Ralph, B. P.; Teng, Y.-H. G.; Berger, W. T.; Galbavy, W.; Elmes, M. W.; Glaser, S. T.; Wang, L.; Rizzo, R. C.; Deutsch, D. G.; Ojima, I. (PLoS One, 2014)

U.S. Patent - Ojima, I.; Deutsch, D.; Kaczocha, M.; Berger, W. T.; Rizzo, R.; Balius, T. E. (Alpha and gamma-truxillic and derivatives and pharmaceutical compositions thereof, 2019)

(untitled) - Kim, J.; Bogdan, D. M.; Elmes, M. W.; Awwa, M.; Yan, S.; Che, J.; Lee, G.; Deutsch, D. G.; Rizzo, R. C.; Kaczocha, M.; Ojima, I. (PLoS One, 2019)

(untitled) - Priebe, A.; Hunke, M.; Tonello, R.; Sonawane, Y.; Berta, T.; Natarajan, A.; Bhuvanesh, N.; Pattabiraman, M.; Chandra, S. (J. Pain Res., 2018)

(untitled) - Yuan, X.; Lin, L.; Zhang, X.; Deng, S. (Phytochem. Lett., 2014)

(untitled) - Matta, A.; Chammingkwan, P.; Singh, B. K.; Terano, M.; Kaneko, T.; Taniike, T. (Appl. Catal., A, 2018)

(untitled) - Wang, Z.; Miller, B.; Mabin, M.; Shahni, R.; Wang, Z. D.; Ugrinov, A.; Chu, Q. R. (Sci. Rep., 2017)

(untitled) - Liu, Q.; Li, N.; Yuan, Y.; Lu, H.; Wu, X.; Zhou, C.; He, M.; Su, H.; Zhang, M.; Wang, J.; Wang, B.; Wang, Y.; et al. (J. Med. Chem., 2012)

(untitled) - Chen, D.; Liao, J.; Li, N.; Zhou, C.; Liu, Q.; Wang, G.; Zhang, R.; Zhang, S.; Lin, L.; Chen, K.; Xie, X.; Nan, F.; et al. (Proc. Natl. Acad. Sci. U. S. A., 2007)

(untitled) - de Graaf, C.; Donnelly, D.; Wootten, D.; Lau, J.; Sexton, P. M.; Miller, L. J.; Ahn, J.-M.; Liao, J.; Fletcher, M. M.; Yang, D.; Brown, A. J. H.; Zhou, C.; et al. (Pharmacol. Rev., 2016)

(untitled) - Poplata, S.; Tröster, A.; Zou, Y.-Q.; Bach, T. (Chem. Rev., 2016)

(untitled) - Sokolova, A.; Pavlova, A.; Komarova, N.; Ardashov, O.; Shernyukov, A.; Gatilov, Y.; Yarovaya, O.; Tolstikova, T.; Salakhutdinov, N. (Med. Chem. Res., 2016)

(untitled) - Zhang, F.; Jia, Y. (Tetrahedron, 2009)

(untitled) - Cohen, M. D.; Schmidt, G. M. J.; Sonntag, F. I. (J. Chem. Soc., 1964)

(untitled) - Schmidt, G. M. J. (Pure Appl. Chem., 1971)

(untitled) - Ramamurthy, V.; Venkatesan, K. (Chem. Rev., 1987)

(untitled) - Pagire, S. K.; Hossain, A.; Traub, L.; Kerres, S.; Reiser, O. (Chem. Commun., 2017)

(untitled) - Lei, T.; Zhou, C.; Huang, M.-Y.; Zhao, L.-M.; Yang, B.; Ye, C.; Xiao, H.; Meng, Q.-Y.; Ramamurthy, V.; Tung, C.-H.; Wu, L.-Z. (Angew. Chem., Int. Ed., 2017)

(untitled) - García-Montero, A.; Rodriguez, A. M.; Juan, A.; Velders, A. H.; Denisi, A.; Jiménez-Osés, G.; Gómez-Bengoa, E.; Cativiela, C.; Gómez, M. V.; Urriolabeitia, E. P. (ACS Sustainable Chem. Eng., 2017)

(untitled) - Roiban, D.; Serrano, E.; Soler, T.; Grosu, I.; Cativiela, C.; Urriolabeitia, E. P. (Chem. Commun., 2009)

(untitled) - Serrano, E.; Juan, A.; García-Montero, A.; Soler, T.; Jiménez-Márquez, F.; Cativiela, C.; Gomez, M. V.; Urriolabeitia, E. P. (Chem. – Eur. J., 2016)

(untitled) - Carrera, C.; Denisi, A.; Cativiela, C.; Urriolabeitia, E. P. (Eur. J. Inorg. Chem., 2019)

(untitled) - Ando, R.; Hama, H.; Yamamoto-Hino, M.; Mizuno, H.; Miyawaki, A. (Proc. Natl. Acad. Sci. U. S. A., 2002)

(untitled) - Mizuno, H.; Mal, T. K.; Tong, K. I.; Ando, R.; Furuta, T.; Ikura, M.; Miyawaki, A. (Mol. Cell, 2003)

(untitled) - He, X.; Bell, A. F.; Tonge, P. J. (Org. Lett., 2002)

(untitled) - Nienhaus, K.; Nienhaus, G. U.; Wiedenmann, J.; Nar, H. (Proc. Natl. Acad. Sci. U. S. A., 2005)

(untitled) - Adam, V.; Lelimousin, M.; Boehme, S.; Desfonds, G.; Nienhaus, K.; Field, M. J.; Wiedenmann, J.; McSweeney, S.; Nienhaus, G. U.; Bourgeois, D. (Proc. Natl. Acad. Sci. U. S. A., 2008)

(untitled) - Chuang, W.-T.; Chen, B.-S.; Chen, K.-Y.; Hsieh, C.-C.; Chou, P.-T. (Chem. Commun., 2009)

(untitled) - Yampolsky, I. V.; Kislukhin, A. A.; Amatov, T. T.; Shcherbo, D.; Potapov, V. K.; Lukyanov, S.; Lukyanov, K. A. (Bioorg. Chem., 2008)

(untitled) - Li, X.; Chung, L. W.; Mizuno, H.; Miyawaki, A.; Morokuma, K. (J. Phys. Chem. B, 2010)

(untitled) - Yale, H. L. (J. Med. Chem., 1958)

(untitled) - Wang, J.; Sánchez-Roselló, M.; Aceña, J. L.; del Pozo, C.; Sorochinsky, A. E.; Fustero, S.; Soloshonok, V. A.; Liu, H. (Chem. Rev., 2014)

(untitled) - Kokotos, G.; Hsu, Y.-H.; Burke, J. E.; Baskakis, C.; Kokotos, C. G.; Magrioti, V.; Dennis, E. A. (J. Med. Chem., 2010)

(untitled) - Plöchl, J. (Ber. Dtsch. Chem. Ges., 1883)

(untitled) - Plöchl, J. (Ber. Dtsch. Chem. Ges., 1884)

(untitled) - Erlenmeyer, E., Jr (Justus Liebigs Ann. Chem., 1893)

(untitled) - Carter, H. E. (Org. React., 1946)

Advances in Heterocyclic Chemistry - Filler, R. (Recent Advances in Oxazolone Chemistry, 1965)

(untitled) - Rao, Y. S.; Filler, R. (Synthesis, 1975)

Chemistry of Heterocyclic Compounds - Rao, Y. S.; Filler, R. (Oxazolones, 1986)

(untitled) - Kim, Y.; Ko, Y. H.; Jung, M.; Selvapalam, N.; Kim, K. (Photochem. Photobiol. Sci., 2011)

(untitled) - Prokof'ev, E. P.; Karpeiskaya, E. I. (Tetrahedron Lett., 1979)

(untitled) - Bondi, A. (J. Phys. Chem., 1964)

(untitled) - Blanco-Lomas, M.; Campos, P. J.; Sampedro, D. (Org. Lett., 2012)

(untitled) - Haasbroek, P. P.; Oliver, D. W.; Carpy, A. J. M. (J. Chem. Crystallogr., 1998)

(untitled) - Asiri, A. M.; Akkurt, M.; Khan, I. U.; Arshad, M. N. (Acta Crystallogr., Sect. E: Struct. Rep. Online, 2009)

(untitled) - Asiri, A. M.; Ng, S. W. (Acta Crystallogr., Sect. E: Struct. Rep. Online, 2009)

(untitled) - Roiban, G.-D.; Serrano, E.; Soler, T.; Aullón, G.; Grosu, I.; Cativiela, C.; Martínez, M.; Urriolabeitia, E. P. (Inorg. Chem., 2011)

(untitled) - Haasbroek, P. P.; Oliver, D. W.; Carpy, A. J. M. (J. Mol. Struct., 2004)

(untitled) - Hanson, A. W. (Acta Crystallogr., Sect. B: Struct. Crystallogr. Cryst. Chem., 1977)

(untitled) - Chatterjee, T.; Mandal, M.; Gude, V.; Bag, P. P.; Mandal, P. K. (Phys. Chem. Chem. Phys., 2015)

(untitled) - Singh, A.; Rajbongshi, B. K.; Ramanathan, G. (J. Chem. Sci., 2015)

(untitled) - Stoermer, R.; Bachér, F. (Ber. Dtsch. Chem. Ges. B, 1922)

(untitled) - Stoermer, R.; Bachér, F. (Ber. Dtsch. Chem. Ges. B, 1924)

Modern Carbonylation Methods - Kollár, L. (Wiley-VCH, 2008)

Handbook of Organopalladium Chemistry for Organic Synthesis - Mori, M. (Wiley-Interscience)

Applied Homogeneous Catalysis with Organometallic Compounds - Beller, M. (Wiley-VCH)

(untitled) - Urriolabeitia, E. P.; Laga, E.; Cativiela, C. (Beilstein J. Org. Chem., 2012)

SAINT, Version 5.0 ed (Bruker Analytical X-Ray Systems, 1998)

SADABS, Program for absorption and other corrections (Göttingen University, 1996)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. A: Found. Crystallogr., 1990)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. A: Found. Crystallogr., 2008)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. C: Struct. Chem., 2015)